2001
DOI: 10.1046/j.1365-2672.2001.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat and salt stress in the food pathogen Bacillus cereus

Abstract: Aims: The effects of stresses imposed on bacterial contaminants during food processing and treatment of packaging material were evaluated on the food pathogen Bacillus cereus. Methods and Results: Conditions were established which allowed the cells to adapt to heat, ethanol and hydrogen peroxide stresses, but not to osmotic shock. Cross protection between stresses indicated a clear hierarchy of resistance with salt protecting against hydrogen peroxide, which protected against ethanol, which protected against h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 29 publications
(38 reference statements)
1
58
0
Order By: Relevance
“…However, the potential of Bacillus to become more resistant to stresses challenges the effectiveness of minimal processing. Several studies have demonstrated that exposure to mild stressing conditions can result in the increased resistance of both mesophilic and psychrotolerant members of the B. cereus group (2,3,5,21,22). These studies used optimal culturing temperature during mild stress exposure to investigate the adaptive stress responses.…”
mentioning
confidence: 99%
“…However, the potential of Bacillus to become more resistant to stresses challenges the effectiveness of minimal processing. Several studies have demonstrated that exposure to mild stressing conditions can result in the increased resistance of both mesophilic and psychrotolerant members of the B. cereus group (2,3,5,21,22). These studies used optimal culturing temperature during mild stress exposure to investigate the adaptive stress responses.…”
mentioning
confidence: 99%
“…Bacteria employ several strategies to adapt to adverse conditions, and upon activation of the so-called adaptive stress response bacteria can become more robust. Exposure to sodium chloride has been shown to induce a protective response in B. cereus, which enables this organism to survive under otherwise lethal conditions (5,8,26). The use of various mild preservation methods in foods is becoming more prevalent, underlining the significance of a better understanding of the stress responses of pathogens to ensure the microbial safety of foods.…”
Section: Cfu Gmentioning
confidence: 99%
“…To date, limited information is available about the underlying mechanisms of the salt stress response of B. cereus. A proteome study performed by Browne and Dowds (5) showed that enzymes involved in the central metabolism were induced in B. cereus NCIMB 11796 during exposure to salt stress. Furthermore, salt stress is known to induce the alternative transcription factor B protein in B. cereus ATCC 14579 (35), suggesting a role for this regulator in the salt stress response of this strain.…”
Section: Cfu Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the mesophilic species B. cereus to gain robustness elicited by mild-stress pretreatment has been well documented (7)(8)(9)(10)(11), and so has the stress-dependent nature of the protective effect induced by such a treatment. Also, the psychrotolerant species B. weihenstephanensis was shown to become more heat resistant after pretreatment with mild stresses (12), and an overlap in the production of selected stress proteins may contribute to this cross-protective phenomenon (12).…”
mentioning
confidence: 99%